Trading on Impulse: The Role of ADHD, Impulsivity, and Gender in Financial Risk and Investment Outcomes - Davoud, Amiri; Sara, Amiri; Lamberto, Briziarelli; Nima, Madani; Barry, Karlsson (Journal of ADHD And Care, 2025)
Background Attention-deficit/hyperactivity disorder (ADHD) in adulthood is increasingly recognized not only as a psychiatric condition but also as a trait with behavioral and occupational implications—particularly in high-stakes, fast-paced financial environments. Traits such as impulsivity, sensation seeking, and altered reward sensitivity may influence decision-making among individuals engaged in stock trading or high-risk investment professions. Objective This systematic review and meta-analytic synthesis aims to investigate the relationship between ADHD, impulsivity, gender differences, and financial risk behavior, with a particular focus on decision-making outcomes in real or simulated trading contexts. Methods Seventeen peer-reviewed studies published between 2008 and 2025 were included. Studies employed behavioral experiments, fMRI paradigms, neurochemical analysis (e.g., glutamate levels), and ecological financial assessments to examine impulsive traits and investment behaviors among adults with and without ADHD. Both clinical samples and occupational cohorts (e.g., brokers, retail investors) were analyzed. The analysis followed PRISMA 2020 guidelines. Results ADHD symptoms—particularly impulsivity and reward hypersensitivity—were associated with increased delay discounting, higher risk-taking, and diminished cognitive control in financial tasks. Neuroimaging data revealed hypoactivation in prefrontal control regions and hyperactivation in reward-related circuits (e.g., ventral striatum). Gender-stratified analyses showed that males with ADHD displayed stronger preference for immediate rewards, higher portfolio turnover, and greater volatility. Preliminary evidence also suggests an overrepresentation of ADHD traits in high-frequency trading roles. Conclusion ADHD-related impulsivity significantly modulates financial risk behavior, particularly in high-stakes and fast-paced contexts such as trading. A convergence of behavioral, neurobiological, and ecological findings suggests that males with ADHD are disproportionately prone to rapid, high-risk financial decisions, whereas females may demonstrate greater regulatory control. These insights underscore the need for gender-sensitive interventions, occupational screening, and tailored psychoeducation. As financial environments become increasingly automated and fast-paced, understanding the neurocognitive vulnerabilities of individuals with ADHD may not only protect personal outcomes but also enhance systemic financial stability.
Keywords: ADHD; impulsivity; trading behavior; financial risk; gender differences; neuroeconomics; reward processing; executive control